Fluoxetine Treatment during In Vitro Fertilization and Culture Increases Bovine Embryonic Development - Choe, Changyong; Kang, Dawon (Journal of animal reproduction & biotechnology (Online), 2014)
K+ channels are involved in the regulation of a variety of physiological functions, including proliferation, apoptosis and differentiation, in mammalian cells. Our previous study demonstrated that the blockage of K+ channels inhibits mouse early embryonic development. This study was designed to identify the effect of K+ channels during bovine embryonic development. K+ channel blockers (tetraethylammonium (TEA), BaCl2, quinine, ruthenium red and fluoxetine) were added to the culture medium during In Vitro fertilization (IVF) for 6 h to first identify the short-term effect of these chemicals. Among K+ channel blockers, fluoxetine, which is used as a selective serotonin reuptake inhibitor, significantly increased the blastocyst formation rate by approximately 6% when compared to control. During the In Vitro maturation (IVM) of immature oocytes and the In Vitro culture (IVC) of embryos, the oocytes and embryos were exposed to fluoxetine for either a short-term (6 h) or a long-term (24 h) to compare the embryonic development in response to exposure time. The 6 h exposure to fluoxetine during IVM did not affect the blastocyst formation rate, but the rate of blastocyst formation was reduced after the 24 h exposure. On the other hand, embryonic development increased approximately 10% in both groups of embryos exposed to fluoxetine for 6 and 24 h during IVC. Taken together, fluoxetine treatment during IVF and IVC, but not IVM, enhances bovine embryonic development. These results suggest that fluoxetine-modulated signals in oocytes and embryos could be an important factor towards enhancing bovine embryonic development.